Associated Factors of Housewives' Behavior in Managing Domestic Waste - Saepudin, Malik; Zalfa, Fara Afrani; Syukur, Abdul; Setyowati , Eny (JURNAL INFO KESEHATAN, 2025)
The volume of waste increases each year; however, household waste management remains inadequate. Housewives are often seen as the key individuals responsible for managing waste at home. Therefore, this study aimed to identify the factors influencing housewives' behavior toward household waste management in Terusan Village, located in the Mempawah Hilir District. This cross-sectional study was conducted from February to June, involving a sample of 85 housewives selected through total sampling. Data were analyzed using the chi-square test. The results indicated no correlation between housewives' behavior in waste management and their age (p-value = 0.414), education level (p-value = 0.107), knowledge (p-value = 0.364), attitude (p-value = 0.439), availability of facilities (p-value = 0.207), or distance to temporary disposal sites (p-value = 0.438). In contrast, the study found a significant correlation between employment status (p-value = 0.001), family income (p-value = 0.007), and family support (p-value = 0.020) with the behavior of housewives in household waste management. The findings suggest that while demographic factors like age, education, and knowledge do not significantly impact waste management practices, employment status, family income, and support from family members do play a critical role in shaping housewives' behavior in waste management in Terusan Village.